Accuracy of intra-operative frozen section in the diagnosis of ovarian mass - Shahla Yazdani; Zinatossadat Bouzari; Mohammad Abedi Samakoosh; Majid Sharbatdaran (Babol University of Medical Sciences, 2015)
Introduction: Ovarian cancer is the most common cause of cancer death from gynecological tumors in Iran. Despite the fact that intra-operative frozen section, which is widely used in diagnosis of ovarian tumors, there are problems associated with the diagnostic procedure in this setting. The aim of this study was to compare the intra-operative frozen section with the permanent histo-pathological sections in the diagnosis of ovarian cancer at Rouhani Hospital in north of Iran. Methods:  The intra-operative frozen section diagnosis was conducted on 126 women with ovarian masses, who underwent surgery between January 2006 and July 2011. The results of the intra-operative frozen section were compared with those of the past histopathological diagnoses of permanent sections as the gold standard. Results: The overall accuracy of intra-operative frozen section diagnosis was 94.4%. There were 0.9% cases with false-positive as well as 1.8% cases with false-negative. The sensitivity and specificity values were 66.7% and 100% for malignant tumors, 80.0% and 95.9 % for borderline tumors, and 99.1% and 90.0% for benign tumors, respectively. All inaccurate diagnoses were for the epithelial tumors. Conclusion: The intra-operative frozen section diagnosis is a reliable method for the surgical management of the patients with an ovarian mass. Diagnostic problems can occur during the intra-operative frozen section examination. The clinicians and pathologists must be aware of the pitfalls of this method therefore, there is an urgent need to establish a good communication among them in order to obtain more accurate results.